Synthesis and Characterization of Metal Tribromoacetates and Their Alkali Metal Derivatives - Jugal Kishore Puri; Rajni Chhoker (Journal of Chemistry)
Complexes of composition Fe2Cl2(O2CCBr3)4, Fe2Cl(O2CCBr3)5, Fe (O2CCBr3)3, [(Me4N)2][Fe (O2CCBr3)4], K[Fe (O2CCBr3)4], Rb[Fe (O2CCBr3)4], Cs[Fe (O2CCBr3)4], [(Me4N)2][Co(O2CCBr3)4], [(Me4N)2][Mn(O2CCBr3)4], [(Me4N)2][Cu(O2CCBr3)4], and [(Me4N)2][Ni(O2CCBr3)4] have been prepared by metathetical reactions using nitromethane as solvent. All these compounds have been characterized by elemental analysis, molar conductance, infrared, reflectance and thermogravimetric studies.